Evaluation of Cytotoxic T-Lymphocyte Antigen-4 (+49A/G) Gene Polymorphism in Chronic Hepatitis B Virus Infection (Iraqi Journal of Medical Sciences, 2020)
Background: Chronic hepatitis B (CHB) infection is associated with the depletion of T cells, resulting in weak or absent virus specific T cells reactivity, which is described as ‘exhaustion’. This exhaustion is characterized by impaired cytokine production and sustained expression of multiple coinhibitory molecules. Cytotoxic T-lymphocyte antigen-4 (CTLA-4) is one of many coinhibitory molecules that can attenuate T cell activation by inhibiting stimulation and transmitting inhibitory signals to T cells.Objective: To explore the effect of CTLA-4+49A/G single nucleotide polymorphism (SNP) on the progression CHB in Iraqi patients.Methods: Blood serum and genomic DNA was isolated from 90 patients with CHB. Tetra-Primer Amplification Refractory System-Polymerase Chain Reaction (ARMS-PCR) was used for amplification and genotyping of CTLA-4 gene using specific primers, and plasma hepatitis B virus (HBV) viral load was investigated by real time PCR, in addition to estimate the hepatitis B e antigen (HBeAg) and anti-HBe by enzyme-linked immunosorbent assay (ELISA).Results: AA genotype was more frequent among uncomplicated than complicated CHB (44.83% versus 28.12%) with a significant difference (OR= 0.315, 95%CI=1.0-0.99, p= 0.048).Conclusion: These data strongly suggested the persistence role of CTLA-4+49 polymorphism against HBV among Iraqi patients.Keywords: CTLA 4, SNP, ARMS-PCRCitation: Mahdi YS, Kadhim HS. Evaluation of cytotoxic T-lymphocyte Antigen-4 (+49A/G) gene polymorphism in chronic hepatitis B virus infection. Iraqi JMS. 2020; 18(2): 101-109. doi: 10.22578/IJMS.18.2.3
Keywords: CTLA 4; SNP; ARMSPCR